2021
DOI: 10.1101/2021.11.22.469490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TheBacillusphage SPβ and its relatives: A temperate phage model system reveals new strains, species, prophage integration loci, conserved proteins and lysogeny management components

Abstract: The Bacillus phage SPβ has been known for about 50 years, but only a few strains are avalible. We isolated four new wild type strains of the SPbeta species. Phage vB_BsuS-Goe14 introduces its prophage into the spoVK locus, previously not observed to be used by SPβ-like phages. We could also reveal the SPβ-like phage genome replication strategy, the genome packaging mode, and the phage genome opening point. We extracted 55 SPβ-like prophages from public Bacillus genomes, thereby discovering three more integrati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…Two recent studies uncovered several novel players of the SPβ lysis-lysogeny decision system [Brady et al, 2021; Kohm et al, 2022]. For instance, a suppressor analysis with a SPβ aimR mutant, which generates more lysogenic cells, revealed that the spontaneous inactivation of the yopN gene, encoding a protein of unknown function, partially restores the control of lysis-lysogeny [Brady et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent studies uncovered several novel players of the SPβ lysis-lysogeny decision system [Brady et al, 2021; Kohm et al, 2022]. For instance, a suppressor analysis with a SPβ aimR mutant, which generates more lysogenic cells, revealed that the spontaneous inactivation of the yopN gene, encoding a protein of unknown function, partially restores the control of lysis-lysogeny [Brady et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a suppressor analysis with a SPβ aimR mutant, which generates more lysogenic cells, revealed that the spontaneous inactivation of the yopN gene, encoding a protein of unknown function, partially restores the control of lysis-lysogeny [Brady et al, 2021]. The same studies identified YopR as the master repressor of the lytic cycle of SPβ [Brady et al, 2021; Kohm et al, 2022]. Although it is unclear how AimR, YopN and YopR interact with each other, it has been proposed that YopN stimulates the repressor activity of YopR [Brady et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also considered as a key industrial organism due to its natural and engineered use in industrial production application, such as in food production (through fermentation), hydrolytic enzymes ( amylases , protases ), and fine chemicals (e.g., riboflavin) [ 18 ]. Despite the importance of B. subtilis strains in the food industry and biotechnology, the temperate phages SPbeta and phi3T are the two main phages that have been involved in research the most in past decades, and the B. subtilis 168 strain is the most frequently preferred host [ 19 , 20 ]. However, no data are available regarding the prevalence, diversity, and inducibility potential of the prophages in large collections of B. subtilis strains.…”
Section: Introductionmentioning
confidence: 99%